2015
DOI: 10.1016/j.amepre.2014.08.026
|View full text |Cite|
|
Sign up to set email alerts
|

Calorie Changes in Chain Restaurant Menu Items

Abstract: Background Supply-side reductions to the calories in chain restaurants are a possible benefit of upcoming menu labeling requirements. Purpose To describe trends in calories available in large U.S. restaurants. Methods Data were obtained from the MenuStat project, a census of menu items in 66 of the 100 largest U.S. restaurant chains, for 2012 and 2013 (N=19,417 items). Generalized linear models were used to calculate: (1) the mean change in calories from 2012 to 2013, among items on the menu in both years;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
32
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 24 publications
3
32
0
1
Order By: Relevance
“…13 Several published studies have used this database to examine trends in nutritional quality of menu items at restaurants over time. 1416 A description of MenuStat methods is published. 17 The sample of restaurant chains used in this study is a balanced panel; all chains offering children's items in each year from 2012 to 2015 were included ( n =45), with children's items designated as any item with “kid,” “child,” or “children” appearing in the menu item or its description.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Several published studies have used this database to examine trends in nutritional quality of menu items at restaurants over time. 1416 A description of MenuStat methods is published. 17 The sample of restaurant chains used in this study is a balanced panel; all chains offering children's items in each year from 2012 to 2015 were included ( n =45), with children's items designated as any item with “kid,” “child,” or “children” appearing in the menu item or its description.…”
Section: Methodsmentioning
confidence: 99%
“…Characteristics of restaurants were extracted from restaurants websites. 14 Restaurant chains were “national” if they were located in all U.S. census regions ( n =26); otherwise, they were “regional” ( n =19). Chains were “full service” if they offered table service ( n =16; e.g., Applebee's); “fast casual” if they offered at least two of the following: non-disposable utensils, onsite food preparation, no table service, or commitment to higher-quality or fresh ingredients or sustainability ( n =6; e.g., Chipotle); and, otherwise, were “fast food” ( n =23; e.g., Burger King).…”
Section: Methodsmentioning
confidence: 99%
“…Our recent study evaluating calorie changes in large chain restaurants 1 found that the number of calories in newly introduced menu items in 2013 decreased by about 60 calories (or 12%) relative to 2012, possibly in anticipation of the final rule about menu labeling from the U.S. Food and Drug Administration required by the 2010 Affordable Care Act. That rule mandates that calorie information be posted on menus and menu boards.…”
Section: Introductionmentioning
confidence: 99%
“…Should the recently observed downward trend in calories of newly introduced menu items in chain restaurants 1 persist (or increase in response to growing consumer demand for low-calorie options once the calories are posted), it could have a sizable impact on population obesity and help to prevent future obesity. In particular, reducing the caloric content of menu items in chain restaurants and other covered food outlets by approximately 60 calories may help to substantively reduce the daily number of excess calories underlying the obesity epidemic in adults (220 calories/day) 16 and children (165 calories/day).…”
Section: Introductionmentioning
confidence: 99%
“…8 Another study demonstrated that the calories in newly introduced menu items at large chain restaurants declined by an average of sixty calories per item (a 12 percent decline) from 2012 to 2013, although very few of these chains voluntarily introduced labeling. 9 …”
mentioning
confidence: 99%